Guyton’s hemodynamic mosaic: crafting fluid management with precision - Rogerio Da Hora Passos; Luciano Ribeiro Pereira Silva; Leonardo Van De Wiel Barros Urbano Andari; Uri Adrian Prync Flato; Murillo Santucci Cesar Assunção; Thiago Domingos Corrêa (Annals of Intensive Care)
Abstract Sheldon Magder’s article on applying Arthur Guyton’s principles to clinical fluid management provides valuable insights into optimizing hemodynamics in critically ill patients. While emphasizing the role of right atrial pressure (RAP) in assessing cardiac output, challenges arise due to RAP’s variable accuracy and the oversimplification of cardiovascular dynamics. Integrating RAP with dynamic assessments and bedside ultrasound can enhance fluid management strategies. Future research should aim to improve RAP’s predictive accuracy and validate its clinical utility for individualized patient care.